Gold nanoparticles combined baker’s yeast as a successful approach for breast cancer treatment - Amany Elwakkad; Amina A. Gamal el Din; Hisham A. Saleh; Noha E. Ibrahim; Mohamed A. Hebishy; Hagar H. Mourad; Mahitab I. El-Kassaby; Howida Sayed Abou-Seif; Ghada M. Elqattan (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background Saccharomyces cerevisiae (S. cerevisiae) has been demonstrated in vitro to sensitize several breast cancer cell lines and to be a safe, non-toxic drug with anti-skin cancer action in mice. Furthermore, plasmonic photothermal treatment using gold nanorods has been authorized as a novel method for in vitro and in vivo cancer therapy. Results When compared to tumor-free rats, the treatment with S. cerevisiae conjugated to gold nanospheres (GNSs) lowered Bcl-2 levels while increasing FasL, Bax, cytochrome c, and caspases 8, 9, and 3 levels. Histopathological results showed changes reflecting the ability of nanogold conjugated heat-killed yeast to induce apoptosis is greater than heat-killed yeast alone as the nanogold conjugated with heat-killed yeast showed no tumor, no hyperplasia, no granulation tissue formation, no ulceration, and no suppuration. Nanogold conjugated with heat-killed yeast-treated breast cancer group displayed normal levels of ALT and AST, indicating relatively healthy hepatic cells. Conclusion Our results proved that nanogold conjugated heat-killed yeast can initiate apoptosis and can be used as a safe non-invasive method for breast cancer treatment more effectively than the yeast alone. This, in turn, gives us new insight and a future hope for the first time that breast cancer can be treated by non-invasive, simple, safe, and naturally originated method and achieves a hopeful treatment and a novel method for in vivo cancer therapy.